KARAKTERISTIK FISIKOKIMIA DAN SENSORIS SNACK BAR TEPUNG LABU KUNING (Cucurbita moschata), TEPUNG JAGUNG (Zea mays) DAN PUREE NANGKA (Artocarpus heterophyllus) - Hartaty, Malikah Meny; Parnanto, Nur Her Riyadi; Yudhistira, Bara; Sanjaya, Adhitya Pitara (Jurnal Teknologi Hasil Pertanian, 2017)
Characteristics of physical properties (texture: hardness), chemical properties (moisture content, ash content, protein content, fat content, carbohydrate content, total calories, antioxidant activity and beta carotene content) and sensory properties of snack bar which added of pumpkin flour, corn flour and jackfruit puree were investigated. Completely Randomized Design (CRD) experimental design with one factor in the form of variation of the amount of pumpkin flour and corn flour that is by formula 1 of 15g pumpkin flour and 25g of corn flour; Formula 2 (F2) of pumpkin flour 10g and corn flour 30g while formula 3 (F3) of pumpkin flour 5g and corn flour 35g were used In this study. The results showed that the variations in the amount of pumpkin flour and corn flour gave effect on the physical properties, chemical properties, and sensory properties of snack bar. Formula 2 is the best snack bar formula with hardness 6,56 N, water content 34,52%, ash of 3.01%, protein content 8,58%, fat content 8,86%, carbohydrate 45,03%, total Calories 294.19 kCal / 100gr, antioxidant activity of 10.72% and beta-carotene content of 787.42 μg / 100gr. Formula snack bar F2 and F3 are preferred samples of panelists on the organoleptic analysis.